Influence of the centralization of public services on the crisis of tourist services - Čanžar, Katja (Academica turistica, 2016)
For the previous eight years, there have been trends in Slovenia to centralize state institutions in bigger towns, as opposed to smaller ones. State institutions are typically placed in bigger urban environments. One part of this environment is the Municipality of Brežice, which is ranked among the top four among Slovenian municipalities offering overnight stays and is seen as a critical administrative and employment centre in its region. The tourist service market in urban environments also depends on local consumers and civil servants that use these services in and outside the tourist season. The purpose of the research is to determine the dependence of tourist service providers on local consumers and civil servants. The tourist sector is often subjected to seasonal variations that cause significant risks for tourist providers. In this research, we are attempting to determine to what extent the use of services by civil servants allows tourist service providers to survive throughout the year, in particular during the off-season. The results of the research show that the centralization of public services affects the change of location of service use, which is significantly connected with the workplace location. The data collected show that civil servants' service use throughout the year enables the survival of tourist service providers outside the tourist season. The centralization of public services can consequently cause a crisis of tourist services in the urban environment since the locals and those em- ployed in urban centres provide constant, even non-seasonal, demand and enable providers to survive throughout the whole year.
Keywords: javni uslužbenci; storitve; tourism; turisti; turistična ponudba; turizem